Pengembangan Pedoman Pelaksanaan Konseling Kelompok Menggunakan Teknik Rational Emotive Therapy (RET) Berbasis E-Book untuk Memfasilitasi Kepercayaan Diri - Ahmad Zaki; Khairiyah Khadijah; Fadhila Rahman (Universitas Batanghari Jambi, 2026)
This research aims to develop guidelines for the implementation of group counseling using E-Book-based Rational Emotive Therapy (RET) to facilitate the confidence of high school students. The research model used is Research and Development (R&D) with a Four-D Model (Define, Design, Develop, and Disseminate) approach. The research subjects were students of Al-Fityah IT High School Pekanbaru, with data collected through interviews, observations, and questionnaires, then validated by media experts, material experts, and linguists. The results of the study showed that the E-Book products developed obtained a very high level of validity from the three validators, with an average validity value of 96.9%. In detail, the validation of media experts reached 97.33%, material experts 97.5%, and linguists 95.87%. This achievement shows that the E-Book is suitable for use as a practical guideline in the implementation of RET-based group counseling because it meets the feasibility aspects of content, appearance, and language. In addition, the results of the practicality test from education practitioners show that this media is easy to use, attractive, efficient, and relevant to the needs of students. Thus, this E-Book is considered effective as an innovation in guidance and counseling services that are adaptive to technological developments and able to increase students' confidence.